Coming through the History: the Revival and Challenge of Spanish Sinology - Li, Qiuyang; Ruiz, Raúl Ramírez (Sinología hispánica. China Studies Review, 2020)
Traditional sinology in Spain is facing the contemporary transition of academic research. It has become an important phenomena and trend in the research of humanities studies, which contains and assimilates contemporary China studies. Starting from the historical origin of Spanish sinology, this article summarizes the development of sinology in contemporary Spain, and analyzes the characteristics and trends of these disciplines. It is found that new Spanish sinology is reviving in the form of China studies, which has been extended in more fields of politics, economics, international relations, sociology and anthropology and so on.